Environmental management and product innovation: The moderating role of the dynamic capability of small manufacturing firms. (10th August 2020) - Mahmud, Muaz; Soetanto, Danny; Jack, Sarah
Abstract: Given the overwhelming concerns on environmental issues, our study attempts to investigate the important role of environmental management practice in the context of product exploration and product exploitation. Additionally, we examine the moderating effect of transformative capability and absorptive capability on the relationship between environmental management and product exploration and exploitation. Based on a survey of 106 managerial-level employees from small manufacturing firms in the United Kingdom (UK), this study found that environmental management practice has a positive direct effect on product exploitation and product exploration. The study also found that (1) transformative capability positively influences the relationship between environmental management and product exploration; (2) absorptive capability negatively influences the relationship between environmental management and product exploitation. From this study, we offer novel insights that extends the existing literature concerning the outcomes of environmental management within the context of product exploration and product exploitation.